Characterization of the complete mitochondrial genome of the medical pipefish Doryichthys boaja Bleeker 1850. Issue 2 (3rd July 2018) - Fang, Yun; Zhu, Lingyan; Chen, Meng; Ge, Yuqing; Zhang, Guangji; Cheng, Rubin
Abstract: In the present study, we reported the complete mitochondrial genome of medical pipefish Doryichthys boaja Bleeker 1850. The complete mitochondrial genome of D. boaja was 16, 562 bp in length and had a base composition of A (31.10%), C (24.14%), G (14.36%), and T (30.40%). Similar to other Syngnathidae species, it contained a typically conserved structure, including 13 protein-coding genes, 2 rRNA genes, 1 control region (D-loop), and 22 tRNA genes. The 13 protein-coding genes encoded 3800 amino acids in total, most of which used the initiation codon ATG except CO1 gene started with GTG. For the stop codon, 6 genes applied TAA as the stop codon, while the other 7 genes used an incomplete stop codon T or TA. The lengths of 12S rRNA and 16S rRNA were 941 bp and 1671 bp, respectively. The control region of D. boaja ranged from 15, 615 bp to 16, 562 bp, which was 948 bp in length. The complete mitochondrial genome of D. boaja provided essential and important molecular data for phylogeography and evolutionary analysis of Syngnathidae Family.